Preparing for the Twenty-First Century - Kennedy, Paul, 1945- (New York Random House Publisher, 1997)
Human history has always been shaped by the growth and migration of populations, by the opportunities and constraints provided by the environment, and by the rise of new technologies. Today, these forces are enmeshed in a state of unprecedented turbulence. World population has more than doubled in the past forty years to reach its current level of 5.5 billion, and it will exceed 8 billion and perhaps even 10 billion early in the next century. How will these vast numbers reshape the world's borders, strain an already fragile ecosystem, and remake politics? New technologies are even now replacing traditional work with radically new systems of production and communication, promising enormous changes in both industrial and traditional agricultural societies.
Include Graphs, Appendix, Notes, Bibliography and Index
Keywords: Twenty-first century -- Population -- Technology--Social aspects -- Twenty-first century